COVID-19-related hospital admission in spouses of partners in at-risk occupations - Bonde, Jens Peter E.; Begtrup, Luise M.; Coggon, David; Jensen, Johan Høy; Flachs, Esben Meulengracht; Jakobsson, Kristina; Nielsen, Christel; Nilsson, Kerstin; Rylander, Lars; Vilhelmsson, Andreas; Petersen, Kajsa Ugelvig; Tøttenborg, Sandra Søgaard (Scandinavian Journal of Work, Environment & Health, 2023)
' ' OBJECTIVE ': 'This study aimed to quantify the risk of COVID-19-related hospital admission in spouses living with partners in at-risk occupations in Denmark during 2020–21. ' ' METHODS ': 'Within a registry-based cohort of all Danish employees (N=2 451 542), we identified cohabiting couples, in which at least one member (spouse) held a job that according to a job exposure matrix entailed low risk of occupational exposure to SARS-CoV-2 (N=192 807 employees, 316 COVID-19 hospital admissions). Risk of COVID-19-related hospital admission in such spouses was assessed according to whether their partners were in jobs with low, intermediate or high risk for infection. Overall and sex-specific incidence rate ratios (IRR) of COVID-19-related hospital admission were computed by Poisson regression with adjustment for relevant covariates. ' ' RESULTS ': 'The risk of COVID-19-related hospital admission was increased among spouses with partners in high-risk occupations [adjusted IRR (IRRadj)1.59, 95% confidence interval (CI) 1.1–2.2], but not intermediate-risk occupations (IRRadj 0.97 95% 0.8–1.3). IRR for having a partner in a high-risk job was elevated during the first three pandemic waves but not in the fourth (IRRadj 0.48 95% CI 0.2–1.5). Sex did not modify the risk of hospital admission. ' ' CONCLUSIONS ': 'SARS-CoV-2 transmission at the workplace may pose an increased risk of severe COVID-19 among spouses in low-risk jobs living with partners in high-risk jobs, which emphasizes the need for preventive measures at the workplace in future outbreaks of epidemic contagious disease. When available, effective vaccines seem essential.
Keywords: at-risk occupation; cohort study; COVID-19; family; industry; job; SARS-Cov-2; virus transmission; vulnerable group